ANALYSIS OF COMPETITIVE STRATEGIES CIGARETTE INDUSTRY IN INDONESIA, STUDY OF GO-PUBLIC COMPANY IN THE GOVERNMENT TRANSITION PERIOD - Muhammad Sulton Aminudin (Politeknik Negeri Sriwijaya, 2020)
The cigarette industry in Indonesia is currently experiencing a pretty heavy pressure, which comes from changes in government policies such as restrictions on importing raw materials, promotional activities, excise tax rates and increasing taxes. The question arises as to the condition of competition in the cigarette industry, during the transition of the SBY presidential administration to president Jokowidodo (2012-2016). Five force porter (1989) is a generic tool to analyze competitive strategies. Then developed by Dobbs (2014) into a more structured, in-depth and strategic insight. This study describes how the performance of core players in the cigarette industry is assessed in terms of profitability ratios during the government transition 2 years before Mr President Susilo Bambang Yudhoyono was replaced by Mr President Jokowi. Then analyze the intensity of competition within the industry by using Dobbs Five Force framework (2014) to assess each side of the industry challenges.